2013
DOI: 10.3138/ptc.2011-63
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists and Physiotherapy Student Placements across Regions in Ontario: A Descriptive Comparison

Abstract: Physiotherapists' participation in physiotherapy students' clinical education varied widely among Ontario regions. Future research could explore whether regional differences are persistent, why they occur, and whether they should be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…11 A recent study in Ontario examined the distribution and type of PT student placements over 1 year relative to the number of practising physiotherapists in the province. 11 The study found substantial differences in placement-type mixes across local health integration networks (LHINs) in Ontario; because the analysis did not include comprehensive data on physiotherapist characteristics and practice areas, however, the researchers were not able to identify the reasons for these differences. 11 Furthermore, the LHINs represent 14 geographical regions in Ontario, which may or may not encompass both rural and urban settings.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…11 A recent study in Ontario examined the distribution and type of PT student placements over 1 year relative to the number of practising physiotherapists in the province. 11 The study found substantial differences in placement-type mixes across local health integration networks (LHINs) in Ontario; because the analysis did not include comprehensive data on physiotherapist characteristics and practice areas, however, the researchers were not able to identify the reasons for these differences. 11 Furthermore, the LHINs represent 14 geographical regions in Ontario, which may or may not encompass both rural and urban settings.…”
mentioning
confidence: 98%
“…11 The study found substantial differences in placement-type mixes across local health integration networks (LHINs) in Ontario; because the analysis did not include comprehensive data on physiotherapist characteristics and practice areas, however, the researchers were not able to identify the reasons for these differences. 11 Furthermore, the LHINs represent 14 geographical regions in Ontario, which may or may not encompass both rural and urban settings. Thus, this research could not directly examine the distribution between rural and urban PT placements.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Areas of practice represented in our sample were very similar to those identified in a population study of Ontario clinical education placements, 16 except that our data set included fewer internships in the musculoskeletal area. Our data set was also similar to the numbers given in the Canadian Institute for Health Information's Physiotherapists in Canada, 2010 report, 17 which found that musculoskeletal and general practice were the most common practice areas and general hospital and private practice were the most common places of employment.…”
Section: Discussionmentioning
confidence: 97%